Does Large-scale Social Restriction Affect Firms' Financial Performance? - Fikri, Muhamad; Noveria, Ana (School of Business and Management Institut Teknologi Bandung, 2021)
Abstract. To prevent the spread of the COVID-19 pandemic, the government has had some large-scale social restrictions (LSSR). As a side effect, many firms experienced a decrease in their revenues, which will decrease their financial performance. This research seeks to investigate how the COVID-19 pandemic affects financial performance of companies listed in the Indonesian stock exchange. To analyze the effect of the COVID-19 pandemic, an ordinary least square (OLS) regression is employed with a dummy variable of the period before and after the pandemic started. Furthermore, to examine the causal effect of LSSR, this study uses the difference-in-difference method with a dummy variable whether the businesses could still operate during the LSSR. The results show that COVID-19 pandemic has a significant negative effect on firms’ financial performance represented by ROA. Secondly, by employing panel-data regression with difference-in-difference, it is found that the LSSR has an insignificant effect on firms’ performance in affected firms. From the results, this research can contribute to the literature to see the effect of the large-scale social restrictions on firms’ financial performance. This research also can be used as a consideration for the government in making future policies to prevent the spread of the COVID-19 pandemic.Keywords: COVID-19 pandemic, difference-in-difference, firms’ financial performance, large-scale social restrictions